Maternal Separation Combined With Limited Bedding Increases Anxiety-Like Behavior and Alters Hypothalamic-Pituitary-Adrenal Axis Function of Male BALB/cJ Mice - Orso, Rodrigo; Creutzberg, Kerstin Camile; Kestering-Ferreira, Erika; Wearick-Silva, Luis Eduardo; Tractenberg, Saulo Gantes; Grassi-Oliveira, Rodrigo (Frontiers in Behavioral Neuroscience, 2020)
Early life stress (ELS) is considered a risk factor for the development of psychiatric conditions, including depression and anxiety disorder. Individuals that live in adverse environments are usually exposed to multiple stressors simultaneously, such as maternal neglect, maltreatment and limited resources. Nevertheless, most pre-clinical ELS models are design to explore the impact of these events separately. For this reason, this study aims to investigate the effects of a combined model of ELS on anxiety-like behavior and hypothalamic-pituitary-adrenal (HPA) axis related targets. From PND 2 to PND 15 BALB/cJ mice were exposed simultaneously to maternal separation (3h per day) and limited bedding (ELS group) or left undisturbed (CT group). Maternal behavior was recorded in intercalated days, from PND 1 to PND 9. Male offspring were tested for anxiety-like behavior from PND 53 to PND 55 in the open field test (OF), elevated plus-maze (EPM) and light/dark test (LD). After behavioral testing, animals were euthanized, and glucocorticoid receptor (Nr3c1), corticotrophin-releasing hormone (Crh) and its receptor type 1 (Crhr1) gene expression in the hypothalamus were measured. Moreover, plasma corticosterone levels were analyzed. We observed that ELS dams presented altered quality of maternal care, characterized by a decrease in arched-back nursing, and increase in passive nursing. Stressed dams also showed an increase in the number of exists from the nest when compared to CT dams. Furthermore, ELS animals showed increased anxiety-like behavior in the OF, EPM and LD. Regarding gene expression, we identified an increase in hypothalamus Crh levels of ELS group when compared to CT animals, while no differences in Nr3c1 and Crhr1 expression were observed. Finally, stressed animals showed decreased levels of plasma corticosterone when compared to CT group. In conclusion, we observed an alteration in maternal behavior in ELS dams. Later in life, animals exposed to the combined model of ELS showed increased levels of anxiety-like behavior. Moreover, the central and peripheral HPA measures observed could possibly indicate a dysregulation in HPA function provoked by ELS exposure.